Highest and Lowest Pitch and Vowel Formants Measurements by Using PRAAT Application - Nasution, Anggita Bella Afrilla; Syarfina, Tengku (Journal of English Language and Education, 2023)
The aims of this study is to describe the steps of measurement in identifying the value of pitch and formant in PRAAT to find out the highest value of vocal pitch and formant. This study employed descriptive qualitative research by using content analysis approach. Content analysis is to organize and elicit meaning from the data collected and to draw realistic conclusion from it (Bengtsson, 2016). Based on the data the results in the formants of the word being pronounced highest is a male and the lowest is female. Meanwhile the pitch highest is a female and lowest is teenage. This study only focus on identifying the highest and lowest pitch and formants from the singer cover (female, male and teenager) on Youtube by applying PRAAT application to calculate in the data that will be analyzed. In addition, the data was descriptive analysis with the presentation of data in the form of numerical tables.